The regulations on cortical activation and functional connectivity of the dorsolateral prefrontal cortex-primary somatosensory cortex elicited by acupuncture with reinforcing-reducing manipulation - Cao, Jingya; Qu, Yuzhu; Chen, Li; Liu, Tianyu; Guo, Jing; Gong, Yulai; Tian, Zilei; Xiong, Jing; Lin, Zhenfang; Yang, Xin; Yin, Tao; Zeng, Fang (Frontiers in Human Neuroscience, 2023)
Introduction: The traditional acupuncture with reinforcing-reducing manipulation is essential for clinical effectiveness, whereas the underlying central mechanism of it remains unknown. This research with multiple-channels functional near-infrared spectroscopy (fNIRS) aims to explore cerebral-response modes during acupuncture with reinforcing-reducing manipulations. Materials and methods: fNIRS data were recorded from 35 healthy participants during the lifting-thrusting reinforcing manipulation, the lifting-thrusting reducing manipulation, and the even reinforcing-reducing manipulation with lifting-thrusting. The general linear model-based (GLM) cortical activation analysis and the functional connectivity (FC) based on region of interest (ROIs) analysis were combined to be conducted. Results: In comparison with the baseline, the results indicated that three acupuncture with reinforcing-reducing manipulations induced the changes in hemodynamic responses and increased FC in the bilateral prefrontal cortex (PFC) and somatosensory cortex. The further comparison revealed that acupuncture with reinforcing-reducing manipulations exhibited different FC patterns within the right dorsolateral prefrontal cortex (DLPFC), between the left primary somatosensory cortex (S1) and left DLPFC, and between the left S1 and left orbitofrontal cortex (OFC). Moreover, the lifting-thrusting reinforcing manipulation and the lifting-thrusting reducing manipulation induced opposite hemodynamic responses in the right DLPFC. Conclusion: These findings verified the feasibility of fNIRS in investigating the functional cerebral activities of acupuncture manipulations, suggesting that the regulations on DLPFC-S1 cortex may be the potential central mechanism for the realization of acupuncture with reinforcing-reducing manipulation’s effect. Trial registration: ClinicalTrials.gov registration number ChiCTR2100051893.